Performance of micro-nanobubbles for synergistic control of ultrafiltration membrane fouling and emerging contaminants during nutrient recovery from biogas slurry - Wancen Liu; Ruohan Xia; Chuanren Qi; Yun Li; Guo Wei; Guoxue Li; Long D. Nghiem; Wenhai Luo (Chemical Engineering Journal, 2026)

Targeting programmed cell death: a novel therapeutic paradigm for cancer based on mode-of-death classification - Xi Qiao; Ting Ye; Tinggai Wu; Xu Han; Tiantian Sun; Haiqiang Wang; Junru Jia; Yuanyuan Dai; Ruohan Yun; Shuo Jiang; Yuming Qin; Zhenzhen Liu; et al. (Apoptosis, 2026)

A novel chitosan and polyferric sulfate composite coagulant for biogas slurry pretreatment by simultaneous flocculation and floatation: Performance and underlying mechanisms - Ruohan Xia; Wancen Liu; Long D. Nghiem; Dingge Cao; Yun Li; Guoxue Li; Wenhai Luo (Water Research, 2024)

Subculture and Etiolation Treatment Promotes Rooting Ability of Upper Branches of Black Locust Crown - Jie Zhang; Ye Zhao; Anan Duan; Wei Wang; Yuhan Sun; Li Dong; Sen Cao; Xiuyu Li; Xiaodi Liu; Chao Han; Saleem Uddin; Wei Bi; et al. (Forest Science, 2023)
The black locust (Robinia pseudoacacia L.) is an economically and ecologically important tree worldwide. However, maturation and position effects affect its asexual reproduction. Despite etiolation treatment and successive subcultures promoting the plant cutting’s rooting rate, whether the promoting effects of aging (upper) branches and young (lower) branches are consistent is unknown. Therefore, we evaluated the relevant rooting ability indicators of tree age effect and its location effect in 26-year-old R. pseudoacacia trees and the current-year branches of different parts. Branches of the upper and lower parts of these trees underwent accelerated germination to generate shoots as explants. We subjected the tissue culture–generated shoots to an etiolation treatment to investigate how the treatment and subculture time affected the rooting ability of the shoot explants induced by different parts of the black locust branch. Tissue culture shoots subjected to the etiolation treatment exhibited a 2–3 day shorter rooting time. Shoots from the upper crown organs achieved a rejuvenation effect, which manifested as enhanced rooting capacity. Our study results provide a theoretical basis for maintaining the juvenility and consistency of clones. Besides having theoretical and practical value, our study also guides the selection of suitable propagation materials for production.

Developing a highly efficient regeneration system for leaves of tissue-cultured tetraploid Robinia pseudoacacia L. - Xiuyu Li; Qi Guo; Chao Han; Juan Li; Li Dong; Sen Cao; Zijie Zhang; Yuhan Sun; Ruohan Wang; Yun Li (In Vitro Cellular & Developmental Biology - Plant, 2022)

Structural architecture of Neoproterozoic rifting depression groups in the Tarim Basin and their formation dynamics - Bizhu He; Cunli Jiao; Taizhu Huang; Xingui Zhou; Zhihui Cai; Zicheng Cao; Zhongzheng Jiang; Junwen Cui; Zhuoyin Yu; Weiwei Chen; Ruohan Liu; Xiaorui Yun; et al. (Science China Earth Sciences, 2019)